The Relationship of E-Governance with The Easy Community of Accessing Public Services (Study on Services in Sukabumi Government) - Purwanto (Jurnal Mantik, 2021)
E-governance has a democratic philosophy in every change. E-Government or electronic government refers to the use of information and communication technology (ICT) to expand access and also government services for the benefit of the community, business people, government officials themselves and other stakeholders. This study uses a qualitative approach with a literature review study method. The results of the study explain that the benefits of this system and feel the benefits. Although this system received a positive response from its users, the lack of socialization from the local government caused a lack of public knowledge of the existence of this system.